2021
DOI: 10.1177/13567667211042641
|View full text |Cite
|
Sign up to set email alerts
|

How service quality and perceived value affect behavioral intentions of ecolodge guests: The moderating effect of prior visit

Abstract: Psychographic segmentation is popular within the tourism literature. It is useful in describing a prototypical customer, however psychological attributes are hard to detect at the individual level and by front-line staff. This paper tests the viability of prior visits (first-time vs. repeat visits) as a segmentation strategy, given this information is readily available to tourism operators. We test an interaction effect between prior visits, service quality, and perceived value using the ECOSERV model, a well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 98 publications
(123 reference statements)
1
17
0
Order By: Relevance
“…In addition, the hotel's products and services purchased by tourists were good buys in terms of both their eco-friendliness and money. Tourists receive a good return on their money spent on the performance of the lodge's products and services, consistent with Ban et al's [33] determination of perceived value and satisfactory pricing in eco-lodge guests.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, the hotel's products and services purchased by tourists were good buys in terms of both their eco-friendliness and money. Tourists receive a good return on their money spent on the performance of the lodge's products and services, consistent with Ban et al's [33] determination of perceived value and satisfactory pricing in eco-lodge guests.…”
Section: Discussionsupporting
confidence: 77%
“…Another study revealed that a previous visit significantly reduces the relationship between perceived value and customer satisfaction. Perceived value influences customer satisfaction and intentions to revisit or advocate an ecolodge among repeat guests [33]. Therefore, we will emphasize two crucial components that influence the behavioral intention of an eco-friendly hotel, namely, perceived value and tourist satisfaction.…”
Section: Eco-friendly Hotelmentioning
confidence: 99%
“…Customer perceived value has significant and notable impacts on consumer postpurchase behavior [68,69,71,72]. Numerous studies have concluded that GPV is one of the key drivers of environmentally sustainable consumer behaviors [15].…”
Section: Green Perceived Value (Gpv)mentioning
confidence: 99%
“…Studies such as Ban et al (2022); Ryu et al (2012); Teng and Wu (2019); H. Yang et al (2016) have identified a positive relationship between PV and consumer behavioural intentions.…”
Section: Description Of the Illustrative Examplementioning
confidence: 99%